Analisis Ancaman Impor Pakaian Bekas Dari Hong Kong Ke Indonesia: Tinjauan Sistematis Dan Bukti Empiris Data BPS Tahun 2025 - Muhammad Faizal Nur Setiawan (GLOBAL SCIENTS PUBLISHER, 2026)
The import of used clothing poses a real threat to Indonesia’s textile and textile products (TPT) industry and has been prohibited since the issuance of Minister of Trade Regulation No. 51/M-DAG/PER/7/2015. Although regulations have been tightened, the illegal import of used clothing from various countries, including Hong Kong, continues and shows an upward trend. This study aims to analyze the threat of used clothing imports from Hong Kong to Indonesia in terms of trade volume, economic impact on the local industry, and the effectiveness of existing policies. The method used was a Systematic Literature Review (SLR) of 14 scientific journal articles published from 2019 to 2025, combined with an analysis of empirical import data from the Central Statistics Agency (BPS) of the Republic of Indonesia for the year 2025. The research results indicate that over the 10-month period available in 2025, the volume of used clothing imports from Hong Kong via Tanjung Perak Port reached 100,610 kg, exhibiting a fluctuating pattern that suggests importers’ adaptation to government enforcement measures. A sharp decline in April 2025 of 1,764 kg was followed by a steep rise in November and December 2025, reaching 14,385 kg and 15,857 kg, respectively the highest levels of the year. These findings confirm that the threat of imports is persistent and adaptive, thus requiring a structural policy response rather than merely sporadic enforcement. This study concludes that there is a need for strengthened interagency coordination, modernization of port surveillance systems, and the continuous empowerment of the local textile, apparel, and footwear (TAF) industry.